Euro crash : the implications of monetary failure in Europe - Brown, Brendan, 1951- (Basingstoke : Palgrave MacMillan, 2010)
This sequel to'Euro On Trial', shows how European Monetary Union became a main engine of the global credit bubble and puts forward a set of remedies which would reduce the danger of further economic debacle emanating from serious flaws in the present policy-making framework of the European Central Bank.
Includes bibliographical references and index.
Keywords: Economic and Monetary Union; European Central Bank; Monetary unions -- European Union countries; Monetary policy -- European Union countries; European Union countries -- Economic policy